Comparación entre los apósitos kruuse manuka ad y cutimed siltec l en cicatrización de heridas postquirúrgicas en caninos sometidos a ovariohisterectomia y orquiectomía - Bósquez Aguilar, Julissa Nataly (2024)
Ovariohysterectomy and orchiectomy are surgical procedures performed worldwide, where veterinarians apply different techniques with the goal of causing minimal tissue damage and thus facilitating healing processes. Currently, in Ecuador, there is limited knowledge about wound management, with the use of topical and aerosolized healing agents being the most popular. The objective of this research is to compare the effectiveness of Kruuse Manuka AD and Cutimed Siltec L dressings in the healing time of post-surgical wounds. Delayed healing poses a problem that affects a high percentage of canines and requires greater care from their owners in controlling potential infections, which can lead to improper closure, creating spaces between the skin where seromas, hematomas, abscesses, and anatomical plane dehiscence may occur. The research methodology included 60 canine patients, both male and female, randomly selected and divided into groups according to the treatment used. The main variable evaluated was healing time, observing the benefits and adverse effects provided by the dressings. The results obtained indicate that patients treated with Kruuse Manuka AD have an average healing time of 4.8 to 5 days, patients treated with Cutimed Siltec L show an average of 6.8 days, and the control group has an average of 8.6 days for the healing time variable. In conclusion, the Kruuse Manuka AD dressing proved to be more effective in the healing of post-surgical wounds in canines, significantly reducing healing time and infection risk. These findings suggest that the implementation of this dressing can improve wound management in veterinary practice.